2013
DOI: 10.1002/smi.2487
|View full text |Cite
|
Sign up to set email alerts
|

Examining Occupational Stress, Sources of Stress and Stress Management Strategies through the Eyes of Management Consultants: A Multiple Correspondence Analysis for Latent Constructs

Abstract: To date, little research has yet focused in broad assessment for management consultancy professionals. This investigation aims to analyse management consultants' self-perceptions of occupational stress (SPoOS), sources of stress (SoS) and stress management strategies (SMS) and to find latent constructs that can work as major determinants in consultants' conceptualization of SPoOS, SoS and SMS. Measures were completed, including demographics and interviews. Complete data were available for 39 management consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Another drawback is that our participants constituted a small sample, were working with different technologies, and were recruited in only five different companies. Even though our sample size is comparable with that of other qualitative studies (Daniels et al, 2013;Humboldt, Leal, Laneiro, & Tavares, 2013), our data will almost certainly not be representative for the entire population of employees in the industrial sector. As a consequence, the generalizability of the present results should be considered with caution.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 86%
“…Another drawback is that our participants constituted a small sample, were working with different technologies, and were recruited in only five different companies. Even though our sample size is comparable with that of other qualitative studies (Daniels et al, 2013;Humboldt, Leal, Laneiro, & Tavares, 2013), our data will almost certainly not be representative for the entire population of employees in the industrial sector. As a consequence, the generalizability of the present results should be considered with caution.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 86%
“…DiCA is a discriminant analysis extension of correspondence analysis (36) and multiple correspondence analysis (37) and both techniques have been used extensively in the analysis of self-assessments and surveys [e.g. memory (38), stress (39), schizophrenia (40), and opioid abuse (41)]. More importantly, recent work in autism and schizophrenia research (using DiCA) has shown that similar summary scores on self-assessments reflected unique patterns of traits for different populations (42).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational stress, or stress caused by a working environment, is a mental and physical condition that produces negative organizational and individual outcomes (Babatunde, 2013;Beheshtifar & Nazarian, 2013;Dewe et al, 2012;Humboldt et al, 2013;Jehangir et al, 2011;Schyns & Schilling, 2013;Shaw, Erickson, & Harvey, 2011;Subramanian & Nithyanandan, 2009). Occupational stress is the most significant form of stress experienced by people reporting their jobs are very stressful or extremely stressful.…”
Section: Occupational Stressmentioning
confidence: 99%
“…Ineffective leadership and occupational stress are a major concern for both organizations and the global economy (Beheshtifar & Nazarian, 2013). The view that ineffective leadership has adverse effects for individuals in the workplace has been historically correlated (Day & Hamblin, 1964) to increased levels of employee stress (Humboldt et al, 2013). Increasing evidence has revealed a clear link between ineffective leaders, employee turnovers, and employee health problems influenced by stress (Dehue et al, 2012;Owusu-Bempah, 2014;Padilla, 2013;Savic & Pagon, 2008;Schyns & Schilling, 2013).…”
Section: Ineffective Leadership and Occupational Stressmentioning
confidence: 99%
See 1 more Smart Citation